A multi-scale stochastic fracture model for characterizing the tensile behavior of 2D woven composites. (15th November 2018) - Zhou, LiChuan; Chen, MingWei; Liu, Chuang; Wu, HengAn
Abstract: In this paper, a multi-scale stochastic fracture model is presented to study the nonlinear mechanical behaviors of two-dimensional (2D) woven C/SiC composites under uniaxial tension. This model considers the randomly distributed intrinsic flaws and the complex braided structure of composites. In the model, the micro-scale representative volume element (RVE) is developed to compute the effective properties of yarns, which are then used in the meso-scale RVE to capture the macroscopic stress response of woven composites. Weibull distribution law is applied to the material elements to reflect the random flaws. The failure mechanism of composites is identified by analyzing the damage rates and the fracture morphologies of fiber, matrix, and interface. The effects of fiber volume fraction and temperature on fracture strength are predicted and the results demonstrate that the failure location varies as the temperature increase due to the relief of thermal residual stress. The presented model provides an efficient tool for evaluating the mechanical properties of textile composites.